Effects of Acute Oral Exposure to Acrylamide on Histological Structures of the Stomach in Wistar Rats - Sabo,I. J. R (Sociedad Chilena de Anatomía, 2021)
SUMMARY: Acrylamide is a toxic chemical substance with wide implementation in chemical industry. In 2002 the presence of acrylamide was discovered in foods rich in starch which are prepared at high temperatures. The aim of this study was to investigate the histopathological changes in the gastric tissue in Wistar rats induced with injection of oral acrylamide. The research was carried out 6 groups of 5 animals (Wistar rats), two control groups and four experimental groups. Histological changes in the stomach tissue of Wistar rats are seen as a direct slight damage of the surface epithelium, accompanynig inflammatory reaction and renewal of the epithelium. Examined inflammatory and degenerative parameters show a positive correlation with respect to dose and time of exposition to acrylamide. Knowing the mechanism of action of these toxic substances, allows to apply adequate prevention in nutrition and make an appropriate choice of therapeutic methods.